Which Norwegian Enterprises Offer the Poorest and the Best Pension Entitlements? - Midtsundstad, Tove (Nordic Journal of Working Life Studies, 2019)
The National Insurance Scheme (NIS) remains the cornerstone of the Norwegian pension system. The introduction of a mandatory occupational pension in 2006, and the restructuring of the contractual pension (AFP) in 2008, have, however, significantly increased the importance of labor market based pensions. Entitlement to AFP and contributions to occupational pensions are largely determined by individual employers, thus resulting in significant different future pension benefits and opportunities to retire early among employees. This article investigates what characterizes private sector enterprises that offer their employees both entitlement to AFP and a ‘good’ occupational pension, compared with enterprises that only offer a minimum pension. Analyzing data from a survey carried out in 2012 among 1107 private sector companies, I find that companies who offered an occupational pension before such schemes became mandatory in 2006 and companies where the social partners had conducted negotiations concerning pensions, were more likely to offer ‘good’ labor market based pensions. Both of these factors are linked to union strength and strong social partner relations.